235k views
11 votes
2/

For all values of x,
f(x)=2x-3
and
a) Find fg(x).
Simplify and give your answer in the form ax² + b
b) Find gf(x).
Simplify and give your answer in the form ax² + bx + c
g(x) = x² + 1

User Viktorzeid
by
5.7k points

1 Answer

8 votes

Answer:

2/

For all values of x,

f(x)=2x-3

and

a) Find fg(x).

Simplify and give your answer in the form ax² + b

b) Find gf(x).

Simplify and give your answer in the form ax² + bx + c

g(x) = x² + 1

Explanation:

User Mariya James
by
5.8k points